Synchrony and social connection in immersive virtual reality - Tarr, B; Slater, M; Cohen, E (Springer, 2018)
Synchronising movements in time with others can have significant positive effects on affiliative attitudes and behaviors. To explore the generalizability of synchrony effects, and to eliminate confounds of suggestion, competence and shared intention typical of standard laboratory and field experiments, we used an Immersive Virtual Reality (VR) environment. Participants, represented as virtual humans, took part in a joint movement activity with two other programmed virtual humans. The timings of the co-participant characters' movements were covertly manipulated to achieve synchrony or non-synchrony with the focal participant. Participants in the synchrony condition reported significantly greater social closeness to their virtual co-participants than those in the non-synchrony condition. Results indicate that synchrony in joint action causes positive social effects and that these effects are robust in a VR setting. The research can potentially inform the development of VR interventions for social and psychological wellbeing.